Depletion of Numb and Numblike in Murine Lung Epithelial Cells Ameliorates Bleomycin-Induced Lung Fibrosis by Inhibiting the β-Catenin Signaling Pathway - Ianni, Alessandro; Hofmann, Michael; Kumari, Poonam; Tarighi, Shahriar; Al-Tamari, Hamza M; Görgens, André; Giebel, Bernd; Nolte, Hendrik; Krüger, Marcus; Salwig, Isabelle; Pullamsetti, Soni Savai; Günther, Andreas; et al. (Frontiers in Cell and Developmental Biology, 2021)
Idiopatic pulmonary fibrosis (IPF), represents the most aggressive form of pulmonary fibrosis (PF) and is a highly debilitating disorder with a poorly understood aetiology. The lung epithelium seems to play a critical role in the initiation and progression of the disease. Repeated injury of lung epithelial cells prompts type II alveolar cells to secrete pro-fibrotic cytokines, which induces differentiation of resident mesenchymal stem cells into myofibroblasts, thus promoting aberrant deposition of extracellular matrix (ECM) and formation of fibrotic lesions. Reactivation of developmental pathways such as the Wnt-ß-catenin signaling cascade in lung epithelial cells plays a critical role in this process but the underlying mechanisms are still enigmatic. Here, we demonstrate that the membrane associated protein NUMB is required for pathological activation of ß-catenin signaling in lung epithelial cells following bleomycin-induced injury. Importantly, depletion of Numb and Numblike reduces accumulation of fibrotic lesions, preserves lung functions and increases survival rates after bleomycin treatment of mice. Mechanistically, we demonstrate that NUMB interacts with casein kinase 2 (CK2) and relies on CK2 to activate ß-catenin signaling. We propose that pharmacological inhibition of NUMB signaling may represent an effective strategy for the development of novel therapeutic approaches against PF.